A review of productive and reproductive characteristics of indigenous goats in Ethiopia - Dereje, T.; Mengistu, U.; Getachew, A.; Yoseph, M. (2015)
Goat production in Ethiopia contributes significantly to national export earnings and the livelihoods of rural households. In the past, a number of research works were conducted to evaluate and improve the performance of indigenous goats. However, systematically compiled information is not available concerning the level of performance of indigenous goats in the country. In this paper, level of performance for major economic traits of indigenous goats is reviewed and discussed. It is apparent from the information presented in this review that the performance of indigenous goat breeds of Ethiopia is highly variable between different management systems. Many of the research reports show that age at first kidding and kidding intervals appear to be shorter in the traditional systems while reproductive efficiency in terms of growth rate, carcass yield, milk yield, litter sizes and survival rate are higher under improved management systems. In terms of body weight and growth rate, lowland goats are not better than those in the other agro-ecologies. Though productivity of indigenous goats is generally considered as low, there is high potential among the indigenous Ethiopian goat breeds under improved management systems. They also produce skins suitable for production of high quality leather products.